2018
DOI: 10.1002/humu.23682
|View full text |Cite
|
Sign up to set email alerts
|

In silico and in vivo models for Qatari-specific classical homocystinuria as basis for development of novel therapies

Abstract: Homocystinuria is a rare inborn error of methionine metabolism caused by cystathionine β‐synthase (CBS) deficiency. The prevalence of homocystinuria in Qatar is 1:1,800 births, mainly due to a founder Qatari missense mutation, c.1006C>T; p.R336C (p.Arg336Cys). We characterized the structure–function relationship of the p.R336C‐mutant protein and investigated the effect of different chemical chaperones to restore p.R336C‐CBS activity using three models: in silico, ΔCBS yeast, and CRISPR/Cas9 p.R336C knock‐in HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…The results described here are somewhat, but not entirely consistent with the cellular expression studies of p.R336C in HEK and HepG2 cells . Like the current studies, this group also found that p.R336C alteration caused reduced steady state levels of CBS protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results described here are somewhat, but not entirely consistent with the cellular expression studies of p.R336C in HEK and HepG2 cells . Like the current studies, this group also found that p.R336C alteration caused reduced steady state levels of CBS protein.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of p.R336C on the human CBS crystal structure indicates that this alteration is located in an alpha helix and that it forms hydrogen bonds with p.D388 and p.L386 (Figure S1 in Data S1). Human p.R336C expressed in yeast appears stable and functionally inactive, while expression in HEK293T and HEPG2 cells suggest that the mutation causes a reduction in protein stability …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Osmolytes are relatively aspecific and were proved active on different proteins such as cystathionine β-synthase [77], aspartylglucosaminidase [78], adenosine triphosphate (ATP)-binding cassette subfamily A member 3 [79], alpha-1 anti-trypsin [80] in cellular models. Particularly interesting is the example offered by another chemical chaperone, 4-phenyl-butyrate (4-PBA).…”
Section: Pharmacological and Chemical Chaperones: Two Types Of Drugs mentioning
confidence: 99%
“…For this reason, it acts as a "hydrophobic chaperone." It can rescue DeltaF508 cystic fibrosis transmembrane conductance regulator (CFTR) [81], cystathionine β-synthase [77], alpha-1 anti-trypsin [80], ABCC6 protein [82], ATP-binding cassette transporter A1 [83], parathyroid hormone [84], and Wilson protein (Copper-transporting P-type ATPase ATP7B) [85] and the list might not be exhaustive. However, the interaction with hydrophobic patches of unstable proteins can only in part account for the effects of 4-PBA.…”
Section: Pharmacological and Chemical Chaperones: Two Types Of Drugs mentioning
confidence: 99%